Terapi Ruqyah dalam Penyembuhan Korban Hipnotis: Studi Takhrij dan Syarah Hadis - Hoirul Anam Zaelani; Hidayatul Fikra; Muhtar Gojali (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze the hadith narrated by Imam Bukhari no. 5298 about ruqyah which is one way to cure hypnosis. In this hadith, the case that occurred at the time of the Prophet was a former disease caused by ain, but this hadith is relevant to be used as the basis for ruqyah treatment due to hypnosis. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods. The results of the research and discussion show that the hadith that describes the healing of hypnotized victims with authentic quality ruqyah based on takhrij, so that the hadith is accepted and can be used as evidence. The syarah of this hadith explains that the Messenger of Allah ordered to ruqyah people who were affected by diseases caused by the glare of the evil eye (ain's disease). From this study it can be concluded that this hadith can be used as a reference in carrying out ruqyah as an effort to heal victims of hypnosis. This study recommends further research using qualitative methods with a field study approach to prove the effectiveness of ruqyah on victims of hypnosis.